Content Analysis of Religious Articles in the Opinion Column in the Palopo Pos Daily Newspaper - Ria Amelinda (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The purpose of this article is to describe the standard content of religious articles required by the daily newspaper Palopo Pos, and the contents of religious articles submitted by the author of the article in the opinion column in the daily newspaper Palopo Pos. The type of research is classified as qualitative with the research approach used are: linguistic approach, journalistic approach and da'wah approach. The data source for this research is the daily newspaper Palopo Pos and other sources in the form of literature, both related to journalism and linguistics. Furthermore, the data collection method used is documentation and reference tracing. Then processing techniques and data analysis were carried out using content analysis theory by Ole. R. Holsti. According to him, content analysis is used to answer the questions "what, to whom, and how" of a communication process. The results of this study answered questions about the standard content of religious articles required by the daily newspaper Palopo Pos that Palopo Pos did not set certain standards in accepting religious articles. As long as the contents of the written article are to call for goodness and increase faith in Allah SWT, educate readers according to religion and without creating fights against other religions, then anyone's article about religion can be published. Furthermore, from the analysis of the several articles studied, all of the articles all lead to religious issues and social issues that are currently being discussed in society. These themes try to find common ground so that a merciful Islam can be carried out in a calm, peaceful and peaceful manner by all Muslims in Indonesia as well as non-Muslims, so that peace can be created between religious communities and a nation that upholds the value of diversity in frame of Pancasila values.